2012
DOI: 10.1016/j.preteyeres.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-CNS connections: Implications in the pathogenesis of diabetic retinopathy

Abstract: Diabetic retinopathy is the fourth most common cause of blindness in adults. Current therapies, including anti-VEGF therapy, have partial efficacy in arresting the progression of proliferative diabetic retinopathy and diabetic macular edema. This review provides an overview of a novel, innovative approach to viewing diabetic retinopathy as the result of an inflammatory cycle that affects the bone marrow (BM) and the central and sympathetic nervous systems. Diabetes associated inflammation may be the result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 142 publications
(145 reference statements)
3
37
0
Order By: Relevance
“…The contribution of bone marrow-derived cells to the acceleration of retinopathy is well established [45]. We also have shown that diabetes skews hematopoiesis towards the generation of more pro-inflammatory monocytes, fewer anti-inflammatory monocytes and lower numbers of reparative progenitor cells [1519]. Bone marrow progenitors from diabetic mice generate higher numbers of myeloid colonies, which is attributed to increased levels of M-CSF and inflammatory cytokines such as IL-1β, IL-27 and IFN-γ in the bone marrow microenvironment [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of bone marrow-derived cells to the acceleration of retinopathy is well established [45]. We also have shown that diabetes skews hematopoiesis towards the generation of more pro-inflammatory monocytes, fewer anti-inflammatory monocytes and lower numbers of reparative progenitor cells [1519]. Bone marrow progenitors from diabetic mice generate higher numbers of myeloid colonies, which is attributed to increased levels of M-CSF and inflammatory cytokines such as IL-1β, IL-27 and IFN-γ in the bone marrow microenvironment [17].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, classical pro-inflammatory Ly6C hi /CCR2 + monocytes lack CX3CR1 expression. We have consistently shown that diabetes skews hematopoiesis towards a myeloid phenotype with an increased infiltration of inflammatory CCR2 + monocytes in the retina [1519]. …”
Section: Introductionmentioning
confidence: 99%
“…Acellular capillaries are a pathologic result typical of the loss of both pericytes and endothelial cells in diabetic retina, and their quantification is a useful way to assess the extent of retinopathy [34]. This study further determined whether chrysin blocked the formation of acellular capillaries in trypsin digested retina of db/db mice.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, in eyes with diabetic retinopathy, progressive loss of endothelial cells and pericytes leads to formation of naked basement membrane tubes. These naked basement tubes become acellular capillaries with irreversible retinal ischemia (Douglas et al, 2012). Thus, there is likely a limited window of opportunity for stem cell treatment to reverse or limit the structural damage within the retina.…”
Section: Pathogenesis and Remodeling Of The Retina In Diseasementioning
confidence: 99%
“…circulating endothelial progenitor cells, was found to be defective due to a diabetes-associated reduction in phosphorylation and intracellular redistribution of vasodilator-stimulated phosphoprotein (VASP), an actin motor protein required for cell migration (LiCalzi et al, 2008). In fact, a defect in the migration of circulating endothelial progenitor cells might contribute to the development of diabetic retinopathy and other disorders (Douglas et al, 2012). Recent studies have shown that bone marrow-derived circulating pro-inflammatory monocytes are increased in diabetes while circulating endothelial progenitor cells (also called circulating angiogenic cells) are trapped in the bone marrow (Hazra et al 2013; Chakravarthy et al, 2016).…”
Section: Types Of Bone Marrow Stem Cellsmentioning
confidence: 99%